Structured web based e-learning tool - Sitti Fatimah Mohamed Sa’ad. (2011)
This report is concerned with the development of the Structured Web Based E-Learning Tool (SWELT). This training portal is a composite tool that supports the rapid development of technologies and vocational demands of specialized skills that engineers need to renew frequently. The solution for an E-Learning portal adapts well to the needs of continuing training, as it can be undertaken in parallel with other work that engineers have to do. The objective of this project is to create a training portal for an organization and incorporating a topic on Advanced Signal Integrity (SI) – High Speed Digital Design to provide a realistic simulation for this tool. The development of SWELT is based on WAMP Server customized with other web parts developed in XML and PHP which support the integration with the overall database.